PEMETAAN SOSIAL PENDAMPINGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. XYZ DI DESA MEUNASAH MESJID KECAMATAN ACEH BESAR - Z., Nasrul; Adamy, Aulina; Wardiati, Wardiati; Taufik, Taufik (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2022)
PT. XYZ is a state company located in Lhoknga, Aceh Besar District. Before being able to decide on a corporate social responsibility (CSR) program, a social mapping is needed so that the CSR program is right on target. Social mapping was carried out through the Rapid Rural Appraisal method with in-depth interviews and descriptive analysis. The population is the Meunasah Mesjid village community in Lhoknga District. A total of 20 selected resource persons: village heads, village leaders, mosque priests, youth leaders, PKK (Family Welfare Empowerment) heads, farmers, fishermen, ranchers, tourism business actors, BUMG heads (village-owned enterprises), health cadres, organizational management, women leaders, small businesses, day laborers, and employees of PT. XYZ. The results found that all groups/organizations came from the village itself. Figures have better formal and religious education so they have access to local and even national levels. The main livelihood is generally working in the scope of PT. XYZ as contractor and partner. The rest work as seasonal farmers and cake makers.